Reconnect: incubating cultural offers for the digital audiences (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
Digitalisation has been a priority for the cultural and creative sectors in the EU for years. This priority became a vital one for the survival of arts, culture and creative organisations provoked by the crisis of the Covid-19 outbreak. Big institutions as well as small and micro-organisations had to accelerate their adjustment to a digital presence in view of their regular public and new digital audiences. As offers in the digital domain proliferated, competition for the attention of target audiences increased too. This was particularly influenced by newly developed dispositions, digital fatigue and higher expectations of the quality and types of online cultural participation available. The focus of the present article are the results of an incubation project that offered targeted support to three creative organisations in Bulgaria in the period of August 2020 – August 2021. The article demonstrates the value of expert support, researching the audiences and fact-based innovation activities of CCI organisations. Incubation efforts empower organisations to improve their connection to committed and new target audiences. This claim is based on the successful impact assessment of the three pilot offers that benefited directly from the research results of the project. Intercultura Consult continues this effort in a new project empowering cultural organisations to incubate experimental offers (including the digital dimension).